1997
DOI: 10.1016/s0014-5793(97)00499-7
|View full text |Cite
|
Sign up to set email alerts
|

Affinity for α‐tocopherol transfer protein as a determinant of the biological activities of vitamin E analogs

Abstract: a-Tocopherol transfer protein (aTTP), a product of the gene which causes familial isolated vitamin E deficiency, plays an important role in determining the plasma vitamin E level. We examined the structural characteristics of vitamin E analogs required for recognition by aTTP. Ligand specificity was assessed by evaluating the competition of non-labeled vitamin E analogs and a-[ 3 H|tocopherol for transfer between membranes in vitro. Relative affinities (/J/?/?-a-tocopherol = 100%) calculated from the degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
398
2
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(421 citation statements)
references
References 18 publications
16
398
2
5
Order By: Relevance
“…Hoppe and Krennrich (2000) and Stone et al (2003) found similar results in humans. This is because of the higher affinity of the α-tocopherol transfer protein for the single stereoisomer (-RRR) of natural vitamin E, against the equimolar amounts of the other eight isomers presented in the synthetic form (Hosomi et al, 1997). Furthermore, it is of interest to highlight that the α-tocopherol stereoisomer profile reflects the vitamin E source provided to sows to a higher extent than that supplied to piglets after weaning.…”
Section: Resultsmentioning
confidence: 99%
“…Hoppe and Krennrich (2000) and Stone et al (2003) found similar results in humans. This is because of the higher affinity of the α-tocopherol transfer protein for the single stereoisomer (-RRR) of natural vitamin E, against the equimolar amounts of the other eight isomers presented in the synthetic form (Hosomi et al, 1997). Furthermore, it is of interest to highlight that the α-tocopherol stereoisomer profile reflects the vitamin E source provided to sows to a higher extent than that supplied to piglets after weaning.…”
Section: Resultsmentioning
confidence: 99%
“…For the vitamin E molecules introduced with the diet, these responses depend on specific pathways that are under the influence of the hepatic a-tocopherol transfer protein (a-TTP). As prototype vitamin E binding protein that regulates uptake and trafficking of all the vitamers in liver cells (Morley et al 2008), this protein binds the fully methylated and saturated form a-TOH with at least 10-fold higher affinity than HM and all the T3 forms (Hosomi et al 1997).…”
mentioning
confidence: 99%
“…Although most of the tocopherols and tocotrienols have similar in vitro antioxidant activity (Zingg and Azzi 2004), a-tocopherol is acknowledged as being the most biologically active E vitamer (Hosomi et al 1997). Of the eight possible stereoisomers of atocopherol, RRR-a-tocopherol has the greatest potency in vivo (Burton et al 1998;Brigelius-Flohé and Traber 1999).…”
mentioning
confidence: 99%